Enabling marine spatial data sharing in Malaysia using a collaboration model - Tarmidi, Mohammad Zakri (2016)
Spatial data sharing has become important in managing sustainable planning and development of marine areas, which involve the GIS implementation in the organization, at national and regional level. However, there are limitations in implementing spatial data sharing especially from institutional aspects including institutional collaboration, in identifying stakeholders, understanding their jurisdictions, and GIS capacity in facilitates spatial data sharing. The institutional collaboration involves organizational management in implementing GIS and partnership engagement between marine organizations. This research is an attempt to develop a conceptual collaboration model to enable spatial data sharing in Malaysia’s marine organizations, which integrate three disciplinarians knowledge’s; marine GIS,marine SDI and collaboration engagement process. For data collection and analysis, an exploratory sequential mixed method design was selected. Exploratory sequential mixed method design combined qualitative-quantitative study in data collection and analysis sequentially. This method analysis combined case studies as qualitative method and survey as a quantitative method for data collection and analysis sequentially. Case studies method used semi-structured interview as data collection instrument, with aim to identify the critical issues in implementing GIS and spatial data sharing in Malaysia’s marine organizations. The interview was conducted with sixteen respondents from eleven organizations from Malaysia’s marine and coastal agencies.Thematic and Strength, Weakness, Opportunities and Threats (SWOT) analyses was selected to categories the critical issues and limitations in marine GIS and spatial data sharing implementation, especially in organizational management and technical aspects. Themes analysis was selected to categorized each issues into specific themes,and SWOT analysis selected to categorized the issues into internal (Strength and Weakness) and external (Opportunities and Threats) factors that affecting marine spatial data sharing in Malaysia. The results of case studies show that there were critical issues in GIS implementation in the organizations, issues in organizational implementation and partnership engagement to enable spatial data sharing within and between marine organizations. For survey method, questionnaire was selected as an instrument for data collection, with aim to identify the critical issues in GIS and spatial data sharing implementation and the relationship between these issues with the implementing of spatial data sharing and partnership engagement. The questionnaire was sent to 48 marine organizations in Malaysia, and received 84.4% overall response.Results from questionnaire was analyse in two part, descriptive and inferential analysis. Descriptive analysis used to understand respondent’s background and knowledge in implementing GIS. Results show 86.8% respondents used GIS more than 3 years, 7.9% using GIS less than a year and 2.6% used GIS between one to two years. Results also shows most of respondents understand the importance of spatial data sharing, with 60.5% understand the definition of spatial data sharing, 68.4% aware on the circular on spatial data sharing, 63.1% have knowledge on MaCGDI role, but not aware on the MyGDI implementation (36.84%). For inferential analysis, the results show correlation between respondent’s duration time using GIS with respondent’s knowledge on GIS (r= -0.373, p < 0.05) with r critical = 0.321. Besides that, the results also show the significant correlation between respondent’s knowledge on GIS data with knowledge on GIS technologies (r = 0.665, p < 0.05) with r critical is 0.321 for n = 38. The results also shows the correlation between respondent’s knowledge on GIS with the implementation of spatial data sharing (r = 0.671, p < 0.05, n = 38) where r critical is 0.321. The next result show there is significant correlation between spatial data sharing implementation with cooperation in the organization (r = 0.729, p < 0.05) for r critical is 0.321 for n = 38. The last result show correlation between spatial data sharing implementation with collaboration with other organizations (r = 0.636, p < 0.01) wherer critical is 0.321 at n = 38. Results from the questionnaire showed the issues with spatial data sharing implementation is on institutional and partnership engagement, and shows the significance of collaboration process between organizations and the need for proper planning on GIS in the organization to successfully implement marine spatial data sharing in Malaysia. Findings from result of mixed method shows there were five indicators in enabling spatial data sharing between Malaysia’s marine organizations;(1) spatial enablement and GIS knowledge improvement, (2) the need for GIS strategic planning and development, (3) the need for effective communication within organization, (4) the need of knowledge on spatial data sharing and (5) partnership engagement in enabling spatial data sharing. From the findings, a conceptual collaboration model was proposed to facilitate the marine spatial data sharing, which consist of three main components: (1) marine GIS strategic planning, (2) marine SDI strategies and (3) collaboration strategy. Marine GIS strategic planning consists of four indicators; GIS people empowerment, GIS technologies improvement, GIS data improvement and GIS organizational empowerment. Marine SDI strategies consists of five indicators; people, data, technologies, policies and standard. Collaboration strategy consists of three main indicators; collaboration engagement, capacity building and information management. The proposed collaboration model then was validated using Delphi method, which gets opinion from expert group, on the usability and practicality of the model in Malaysia. Output from the Delphi method shows that the experts agreed that the collaboration model is practical and able to be implemented in Malaysia. This model has important theoretical strength because it explicitly framed the relationship between internal ability of organization in implementing GIS and spatial data sharing and the external ability of collaboration between organizations. This model will be useful and of interest to marine organizations communities that use spatial data and GIS to facilitate their usage.